Comparative Human Development and Gender Equality Performance Analysis of Middle Eastern and North African Countries with Turkey - MIHCI, Hakan; TANER, Mehmet Tolga (International Journal of Economics and Financial Issues, 2014)
The aim of this paper is to concentrate on the very recent development performance of two country groups, namely Middle Eastern and North African countries, and to focus on Turkey in an attempt to determine the position of the country in the context of human development. To achieve this, descriptive statistical analysis is used and existing data is assessed in a comparative way to be more specific about the position of Turkey in her path of human development. The analysis period is restricted to the last five years. As a result, it is found that Turkey is in conjunction with the main trends of the countries under investigation and that it deviates from the standards of European and high human development index group of countries. In addition, Turkey’s human development performance of the country mainly accentuated from its relative backwardness in the gender-based indicators. In this context, the country is not only below the averages of the European, Central Asian and high human development index group countries, but also from the relatively backward Middle Eastern countries as well, and therefore, it seems to conform more to the standards of North African countries. In the case of Turkey, instead of attempting to achieve high growth rates, and henceforth to reach high per capita income levels, it would be better for policy makers to concern with advancing the level of human development through emphasizing education, healthcare services and especially struggling with the prevailing gender inequalities in every aspect of socio-economic life. Keywords: Human Development; Gender Equality; Turkey JEL Classifications: J16; O10; O15